2003
DOI: 10.1074/jbc.m210804200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Myosin Heavy Chain Functionality in the Heart

Abstract: Comparison of mammalian cardiac ␣-and ␤-myosin heavy chain isoforms reveals 93% identity. To date, genetic methodologies have effected only minor switches in the mammalian cardiac myosin isoforms. Using cardiac-specific transgenesis, we have now obtained major myosin isoform shifts and/or replacements. Clusters of non-identical amino acids are found in functionally important regions, i.e. the surface loops 1 and 2, suggesting that these structures may regulate isoform-specific characteristics. Loop 1 alters fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
111
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(125 citation statements)
references
References 45 publications
14
111
0
Order By: Relevance
“…Similar results have been reported by others studying the functional consequences of MHC isoform shift in transgenic mouse hearts, where 75% βMHC was forced expressed [31]. Krenz et al noted that transgenic mice having a 25 to 75% α-to βMHC ratio were healthy and had no apparent defect in overall cardiac morphology, suggesting that the transition from α-to βMHC is benign in terms of the overall health of the animals [31]. However, when these hearts were stressed and analyzed for hemodynamic determinants, transgenic hearts with 75% βMHC had significantly reduced contractile ability, as assessed by diminished dp/dt max, compared to non-transgenic controls [32].…”
Section: Functional Consequences Of Myosin Isoform Shiftsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results have been reported by others studying the functional consequences of MHC isoform shift in transgenic mouse hearts, where 75% βMHC was forced expressed [31]. Krenz et al noted that transgenic mice having a 25 to 75% α-to βMHC ratio were healthy and had no apparent defect in overall cardiac morphology, suggesting that the transition from α-to βMHC is benign in terms of the overall health of the animals [31]. However, when these hearts were stressed and analyzed for hemodynamic determinants, transgenic hearts with 75% βMHC had significantly reduced contractile ability, as assessed by diminished dp/dt max, compared to non-transgenic controls [32].…”
Section: Functional Consequences Of Myosin Isoform Shiftsupporting
confidence: 90%
“…Korte et al have shown that the replacement of MHC isoforms from 100% α-to ~80% βMHC, by thyroid manipulation, reduced the power output of the left ventricle by nearly 65%, and the stroke volume and cardiac output by nearly half to the control values obtained from hearts with 100% αMHC [26]. Similar results have been reported by others studying the functional consequences of MHC isoform shift in transgenic mouse hearts, where 75% βMHC was forced expressed [31]. Krenz et al noted that transgenic mice having a 25 to 75% α-to βMHC ratio were healthy and had no apparent defect in overall cardiac morphology, suggesting that the transition from α-to βMHC is benign in terms of the overall health of the animals [31].…”
Section: Functional Consequences Of Myosin Isoform Shiftsupporting
confidence: 68%
“…Ventricular protein was loaded onto a 5% glycerol gel and electrophoresed to separate the ␣-and ␤-MHC proteins. A mouse in which 70% of the ␣-MHC was replaced with ␤-MHC through genetic manipulation (27) was used as a marker. Both transcript and MHC analyses were performed on mice at 15 weeks, and an additional line (ELC1v-wt), defined in previous studies (5,18) Storage solution had the same constituents as relaxing solution plus 10 g/ml leupeptin and 50% (w/v) glycerol.…”
Section: Methodsmentioning
confidence: 99%
“…Increased βMHC expression during cardiac hypertrophy is a well-estab- lished phenomenon and is thought to contribute to the overall poor functioning of the hypertrophic heart (28)(29)(30). To better assess the effects of miR-208a on the expression of βMHC, we employed a mouse strain harboring a βMHC indicator allele, in which the yellow fluorescent protein (YFP) sequence is fused to the Myh7 gene (31).…”
Section: Figurementioning
confidence: 99%